1988
DOI: 10.1212/wnl.38.9.1366
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in multiple sclerosis

Abstract: In a sample of 29 impotent men with multiple sclerosis and erectile problems, penile arterial inflow and venous outflow were within normal limits. In 26 patients, the pudendal evoked potential (PEP) was abnormal, and eight of these also had abnormal bulbocavernous reflex (BCR). Three patients had abnormal PEP and normal BCR, and of these, two had normal and one had abnormal nocturnal erectile activity. The validity of PEP/BCR testing was supported by normal findings in six patients with MS and without erectile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…The other 2 abnormal evaluations were found in a patient with adrenomyeloneuropathy and in a patient with stenosis of the spinal canal. We came to the same conclusion as Kirkeby [9].…”
Section: Is a Normal Rigiscan Registration Always A Proof Of Psychogesupporting
confidence: 65%
“…The other 2 abnormal evaluations were found in a patient with adrenomyeloneuropathy and in a patient with stenosis of the spinal canal. We came to the same conclusion as Kirkeby [9].…”
Section: Is a Normal Rigiscan Registration Always A Proof Of Psychogesupporting
confidence: 65%
“…It has been shown that intracavernous injection of papaverine gives erection in almost all multiple sclerosis patients with erectile dysfunction (Kirkeby et al, 1988). Insufficient arterial inflow or venous outflow problems do not appear to be involved (Kirkeby et al).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Pathological bulbocavernosal, or anal sphincter reflexes, or ab normal pudendal evoked potentials (Bemelmans et al,1991;Kirkeby et al, 1988;Vas, 1969), as well as pathological urodynamic findings or reduced urethral sensitivity thresholds (Brekkan et al, 1988;Lundberg et al, 1982;Rydin et al,1981), give further evidence of involvement of those parts of the nervous system controlling pelvic floor structures.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…However, this test is time-consuming, cumbersome, relatively expensive, and its result can be affected by psychological factors, sleep disorders, drugs taken, and hypogonadism [1, 2, 3, 4, 5, 6, 7]. In addition, adequate nocturnal erection may be observed in patients with organic impotence, especially in patients with neurogenic impotence [8]. Furthermore, it remains unclear whether the result of a nocturnal penile erection test is a valid indicator of erectile potential in erotic and sexual circumstances [9].…”
Section: Introductionmentioning
confidence: 99%